Little green ebook An easy rawlins mystery. - Mosley, Walter (Easy Rawlins, 2013)
When Walter Mosley burst onto the literary scene in 1990 with his first Easy Rawlins mystery, Devil in a Blue Dress —a combustible mixture of Raymond Chandler and Richard Wright—he captured the attention of hundreds of thousands of readers (including future president Bill Clinton). Eleven books later, Easy Rawlins is one of the few private eyes in contemporary crime fiction who can be called iconic and immortal. In the incendiary and fast-paced Little Green , he returns from the brink of death to investigate the dark side of L.A.’s 1960s hippie haven, the Sunset Strip. We last saw Easy in 2007’s Blonde Faith , fighting for his life after his car plunges over a cliff. True to form, the tough WWII veteran survives, and soon his murderous sidekick Mouse has him back cruising the mean streets of L.A., in all their psychedelic 1967 glory, to look for a young black man, Evander “Little Green” Noon, who disappeared during an acid trip. Fueled by an elixir called Gator’s Blood, brewed by the conjure woman Mama Jo, Easy experiences a physical, spiritual, and emotional resurrection, but peace and love soon give way to murder and mayhem. Written with Mosley’s signature grit and panache, this engrossing and atmospheric mystery is not only a trip back in time, it is also a tough-minded exploration of good and evil, and of the power of guilt and redemption. Once again, Easy asserts his reign over the City of (Fallen) Angels.